Beobachtungen und Gedanken zu geomorphologischen Konvergenzen in Polar- und Wärmewüsten - Meckelein, Wolfgang (ERDKUNDE, 1965)
The paper reports and evaluates observations from Western Spitsbergen in relation to the structure of the polar Hammada, rock weathering, foliation and formation of salt crusts, the role played by fine grain material and relative stability of geomorphological features. These convergences (similarities) of minor landforms and geomorphological processes are not simply the outcome of comparable conditions of aridity. Similarities of forms are not necessarily brought about by identical causes. It can be shown that in the complex of geomorphologically effective climatic elements some factors are interchangeable without influencing the final geomorphological outcome. Especially in denudation processes climate frequently acts merely indirectly. It gives rise to certain soil characteristics which in turn influence the type of denudation. The effect of fluviatile processes always exceeds that of wind; this is so in polar desserts as well as in the desserts and extreme desserts of the global dry belt. For a true appreciation of interrelationships between climate and landforms detailed micro geomorphological and micro-climatic investigations play an important role.